ANALISIS STRUKTUR GERAK TARI GALOMBANG DI SANGGAR SENI TUAH SAIYO KOTA PADANG SUMATERA BARAT - Septhiani Fransiska Putri; Mansyur, Herlinda (Universitas Negeri Padang, 2026)
Galombang Dance is a traditional dance from Minangkabau which is used as a dance to welcome respected guests and has a strong symbolic meaning in the social life of the community. With the development of the times, a creative process has occurred in the development of Galombang Dance in various art venues, one of which is at the Tuah Saiyo Art Studio in Padang City. This study aims to describe and analyze the movement structure of the Galombang Dance at the Tuah Saiyo Art Studio in Padang City, West Sumatra. The method used is a qualitative method with a descriptive analytical approach. Data collection techniques include observation, interviews, and documentation. The analysis of the movement structure was carried out using Ben Suharto's theory, which includes the relationship between basic elements and grammatical hierarchical relationships in movement. The results of the study show that the movement structure of the Galombang Dance at the Tuah Saiyo Art Studio consists of attitudes and movements of the head, body, hands, and feet that are interrelated and form motifs, phrases, sentences, and movement groups.